Genetic diversity and geographical genetic diversity in Colombian accessions of Lippia alba (Mill.) N.E. Brown - Cardona-Montoya, José Omar; Muñoz, Jaime Eduardo (Revista de Ciencias Agrícolas, 2019)
Bushy matgrass (Lippia alba, Verbenaceae) is a promising plant genetic resource, by their active compounds. The present document studied the molecular genetic diversity and spatial genetic structure of two contrasting populations of L. alba in Colombia. Eight RAM, evaluated total DNA of 59 accessions of non-cultivated plants collected in two Colombia regions, Chicamocha and Sumapaz. The expected average heterozygosity (or average heterozygosity genetic diversity of Nei) for the sample had low value (0.0≤He=0.2467≤0.5). The values of molecular diversity (MD) indicated values in the range of 0.1219 to 0.3425 for seven RAM. The frequency of variants is based on an effective number of alleles [Ae] and expected heterozygosity [He], genetic diversity by locus (hj=1-p2-q2) had maximum values (near 0.5) in the primers ACA, AG, CGA, and CEC. RAM suitably analyzed Lippia alba as an endemic genetic resource. A DNA bank composed of 59 Colombian accessions from Lippia alba was set up. The analysis of the spatial global structure shows that the subpopulation Sumapaz is structured, whilst the subpopulation Chicamocha, is in the structuring process. The results suggest in all cases the need for implementing: a) exchange of gene-seed, (b) gene banks with maximum genetic variability and c) induce genetic diversity.